2011
DOI: 10.1210/jc.2011-0127
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of a Novel Inactivating Mutant Thyrotropin Receptor Allele with Two Thyroid Peroxidase Mutations: A Genotype-Phenotype Correlation

Abstract: TSHR and TPO gene mutations were identified alone and together in individuals of a consanguineous kindred. Homozygotes for the TSHR and a compound heterozygote for the TPO mutations were hypothyroid. The mild hyperthyrotropinemia of heterozygotes for the mutant TSHR allele was not aggravated by the coexistence of a TPO defect in one allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 12 publications
3
31
0
Order By: Relevance
“…Coexistence of mutations in TPO (Sriphrapradang et al, 2011) and GNAS (Lado-Abeal et al, 2011), in addition to mutations in TSHR, has been reported in the same individuals. In those reports, the coexistence of mutated TPO and TSHR in the same individuals belonging to the same kindred did not aggravate the severity of the RTSH phenotype (Sriphrapradang et al, 2011); similar observations were made for the presence of a monoallelic TSHR mutation coexisting with a GNAS mutation (Lado-Abeal et al, 2011). It is therefore suggested that in cases where TSHR mutations do not explain the phenotype, additional genes that are involved in thyroid hormone synthesis be screened.…”
Section: Differential Diagnosismentioning
confidence: 68%
See 3 more Smart Citations
“…Coexistence of mutations in TPO (Sriphrapradang et al, 2011) and GNAS (Lado-Abeal et al, 2011), in addition to mutations in TSHR, has been reported in the same individuals. In those reports, the coexistence of mutated TPO and TSHR in the same individuals belonging to the same kindred did not aggravate the severity of the RTSH phenotype (Sriphrapradang et al, 2011); similar observations were made for the presence of a monoallelic TSHR mutation coexisting with a GNAS mutation (Lado-Abeal et al, 2011). It is therefore suggested that in cases where TSHR mutations do not explain the phenotype, additional genes that are involved in thyroid hormone synthesis be screened.…”
Section: Differential Diagnosismentioning
confidence: 68%
“…We found up to 2.4% carriers of two known mutations in a highly consanguineous population in the northern region of Israel (Tenebaum-Rakover et al, 2009). Moreover, the coexistence of two different novel mutations of TSHR in each of two separate clans has been shown (Sriphrapradang et al, 2011). In view of these data, it may be speculated that the occurrence of inactivating TSHR mutations in certain populations is not so rare, and therefore screening for TSHR mutations is indicated in cases with non-autoimmune subclinical hypothyroidism in those populations.…”
Section: Prevalence Of Loss-of-function Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the mutations are missense mutations, but deletions and insertions have been identified as well [5].…”
Section: Introductionmentioning
confidence: 99%